Students’ Consumption of Beverages and Snacks at School and Away from School: A Case Study in the North East of Italy - Losasso, Carmen; Cappa, Veronica; Neuhouser, Marian L.; Giaccone, Valerio; Andrighetto, Igino; Ricci, Antonia (Frontiers in Nutrition, 2015)
In North-East Italy (the Veneto region) several public school nutrition policies have been developed to reduce the consumption of high caloric snacks and beverages. However, little is known about whether the policies actually influence students’ dietary behaviours. In order to address this point, a multi-centre cross-sectional survey of 691 Italian students was conducted. Students completed the Beverage and Snack Questionnaire (BSQ), which assesses the consumption of beverages and snacks at school and out-of-school. Three levels Poisson Models with random intercept with students (level 1 units) nested into classroom (level 2 units), and nested into schools (level 3 units), were used to examine the influence of the school setting versus the out-of-school environment (independent variable) on students’ consumption of sweet beverages, snacks, milk based beverages, low carbohydrate drinks, fruit and vegetables (dependent variable) (p≤0.05). The results showed a significantly higher consumption of sweet beverages, snacks, milk-based beverages, low-carbohydrate drinks, fruit and vegetables out-of-the school, suggesting a school-protective association Thus, the policies aimed to limit or deny access to unhealthy foods in the school environment may play an important role in promoting more healthful dietary patterns for school children. Additional studies should be conducted to compare students’ dietary behaviours between schools with nutrition policies to those without nutrition policies.